The role of albedo and accumulation in the 2010 melting record in Greenland ... - Tedesco, Marco; Fettweis, X.; Van Den Broeke, M. R.; Van De Wal, R. S. W.; Smeets, C. J. P. P.; Van De Berg, W. J.; Box, J. E.; Serreze, M. C. (Columbia University, 2011)
Analyses of remote sensing data, surface observations and output from a regional atmosphere model point to new records in 2010 for surface melt and albedo, runoff, the number of days when bare ice is exposed and surface mass balance of the Greenland ice sheet, especially over its west and southwest regions. Early melt onset in spring, triggered by above-normal near-surface air temperatures, contributed to accelerated snowpack metamorphism and premature bare ice exposure, rapidly reducing the surface albedo. Warm conditions persisted through summer, with the positive albedo feedback mechanism being a major contributor to large negative surface mass balance anomalies. Summer snowfall was below average. This helped to maintain low albedo through the 2010 melting season, which also lasted longer than usual. ...